A new class of rare earth tetrapyrrole sandwich complexes containing corrole and phthalocyanine macrocycles: synthesis, physicochemical characterization and X-ray analysis1. Issue 12 (11th February 2015) - Lu, Guifen; Yan, Sen; Shi, Mengying; Yu, Wenhan; Li, Jing; Zhu, Weihua; Ou, Zhongping; Kadish, Karl M.
<x xml:space="preserve">Abstract</x> The first example of a tetrapyrrole sandwich complex containing corrole macrocycle is prepared and spectroscopically, electrochemically and structurally characterized.